2013
DOI: 10.1186/1749-799x-8-25
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a biphasic injectable bone substitute on the interface strength in a rabbit knee prosthesis model

Abstract: BackgroundIn joint prosthetic surgery, various methods are used to provide implant stability. We used an injectable bone substitute, composed of calcium sulfate/hydroxyapatite, as bone defect filler to stabilize a tibia prosthesis in an experimental rabbit model. The aim of the study was to investigate and compare the stability of prosthetic fixation with and without the use of an injectable bone substitute.MethodsSixteen rabbits were used and the tibia prostheses were implanted bilaterally, one side with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“…Cerament G and Cerament V incorporate gentamicin sulphate (175 mg/10 mL) and vancomycin (66 mg/mL), respectively, and preclinical studies have demonstrated their efficacy in treating infected bone defects 16 and no detrimental effects on osteointegration when used as a coating on implants 17.…”
Section: Introductionmentioning
confidence: 99%
“…Cerament G and Cerament V incorporate gentamicin sulphate (175 mg/10 mL) and vancomycin (66 mg/mL), respectively, and preclinical studies have demonstrated their efficacy in treating infected bone defects 16 and no detrimental effects on osteointegration when used as a coating on implants 17.…”
Section: Introductionmentioning
confidence: 99%
“…Alloplastic bone substitutes, especially hydroxyapatite (HA), alpha-and beta-tricalcium phosphate (α-TCP and β-TCP) and biphasic calcium phosphate ceramics are viable alternatives to autogenous, allogeneic and xenogeneic bone grafts in surgical bone augmentation and replacement (1). Even though they lack some of the qualities of autografts, allografts and xenografts such as osteogenesis and osteoinduction, alloplastic bone substitutes are osteoconductive (2)(3)(4)(5)(6), readily available in different easy-to-use forms (7)(8)(9), and pose no risk of disease transmission or morbidities associated with bone graft harvesting (10)(11)(12). It has been shown that these biomaterials are mainly degraded by the process of phagocytosis, which is affected by the chemical composition and physical characteristics of a biomaterial.…”
mentioning
confidence: 99%
“…For BBSMs, the tissue reaction is formed by the individual reactions towards each of the material compounds. Therefore, aspects such as biodegradation is based on the activity of phagocytes such as macrophages and BMGCs towards the individual compounds (10,12,17,(20)(21)(22)(23)(24)(25)(26). Hence, BBSMs initially induce an inflammatory tissue reaction similar to that of a pure β-TCP material, resulting in a high number of BMGCs and a high degradation rate, at later stages this is followed by a slower degradation rate correlated with lower BMGC numbers at a later, which can be compared to pure HA (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations